Metadata for the beastly business project: illegal wildlife trade, 2021-2023 - Duffy, Rosaleen (UK Data Service, 2023)
The Beastly Business Project focused on IWT in European species, specifically the trade in European brown bears, European eels and songbirds. It delivered new empirical data and a novel analytical framework that synthesises the strengths of two key approaches - political ecology and green criminology. Europe is a key area for sourcing, consuming and transporting wildlife, but this is overlooked in academic and policy debates; instead IWT tends to be presented as a problem of Africa and Asia. In policies to tackle IWT Europe is often identified only as a transit route for wildlife products trafficked from source (typically assumed to be Africa) to consumer (typically assumed to be Asia). This misses the importance of IWT within Europe and in European species. Focusing on IWT in Europe is important because it is a key driver of biodiversity loss, and it has become a prominent policy issue in the EU. Due to ethical constrains the data cannot be shared outside of the project group.